Elemento(III) Derivatives of N-(2-Hydroxy-6-Methyl Benzyl) Alanine - Kandpal, Manju; Nagarkoti, Sangita; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several elemento(III) viz. boron, aluminium, iron, arsenic and antimony derivatives of N-(2-hydroxy-6-methyl benzyl) alanine have been prepared by the interaction of the corresponding elemento (III) isopropoxide with the latter in 1 : 1, 1 : 2 and 1 : 3 molar ratios in benzene medium and characterized by azeotrope, elemental analysis and by IR and PMR spectra.